Effect of the surface treatment on the strength of the single-lap adhesive joints - Doluk , Elżbieta; Rudawska, Anna; Stančeková, Dana (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2021)
The paper analyzed the shear strength of the single-lap adhesive joints made of zinc galvanized coat of steel sheet. Mechanical treatment of the samples was carried out using P120, P180, P220, P400 and P600 abrasive papers. In the experiment were used two variants of surface treatment: with a degreaser and without a degreaser.A two-component epoxy adhesive Epidian 53/IDA/100:40 was used to make the joints.The strength tests were carried out on a Zwick/Roell Z150 testing machine, PN-EN 1465 standard. The article contains also the results of the maximum force and the values of the surface roughness parameters (Ra, Rz, Rq) of the samples prepared without a degreaser. The measurements of surface roughness parameters (Ra, Rz, Rq) were made using a HOMMEL TESTER T1000 profilometer, according to PN-EN ISO 4287. The maximum value of the shear strength (2.70 MPa) was obtained for the samples prepared with P220 abrasive paper using a degreaser and the lowest (1.02 MPa) for the samples prepared with P180 abrasive paper using a degreaser. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)